Development of a Power Operated Black Pepper Thresher - Suma Nair (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 1998)
A power operated black pepper thresher comprising mainly of a threshing drum and a concave; both lined with thermofoam, was developed. It was driven by a O.S-hp, 3-phase, variable speed motor.